2014
DOI: 10.1016/j.cej.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic co-digestion of solid slaughterhouse wastes with agro-residues: Synergistic and antagonistic interactions determined in batch digestion assays

Abstract: Please cite this article as: J.P. Díaz, I.P. Reyes, M.J. Taherzadeh, I.S. Horváth, M. Lundin, Anaerobic co-digestion of solid slaughterhouse wastes with agro-residues: Synergistic and antagonistic interactions determined in batch digestion assays, Chemical Engineering Journal (2014), doi: http://dx.doi.org/10. 1016/j.cej.2014.02.008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(67 citation statements)
references
References 33 publications
2
62
0
3
Order By: Relevance
“…A synergistic effect results in increased CH 4 production from the substrates beyond what is achieved from digestion of each individual component [5,9]. A synergistic effect was observed when co-digesting equal mass fractions of municipal solid waste, slaughterhouse waste, manure, and various crops.…”
Section: Introductionmentioning
confidence: 86%
“…A synergistic effect results in increased CH 4 production from the substrates beyond what is achieved from digestion of each individual component [5,9]. A synergistic effect was observed when co-digesting equal mass fractions of municipal solid waste, slaughterhouse waste, manure, and various crops.…”
Section: Introductionmentioning
confidence: 86%
“…Experimentally, co-digestion of a mixture of cow manure and fruit and vegetable waste (50:50 by weight) produced 450 m 3 ton -1 VS at 35 ±0.5ºC [61], whereas a mixture of buffalo manure and maize silage (70:30 by VS content) at 35 ±1ºC produced 358.23 ±44.15 m 3 [62]. It has also been shown that meadow grass with its biochemical methane potential value of 388 ±30 mL g -1 VS has a yield increase of 114% when codigested with manure in a continuous stirred tank reactor [63], and when a mixture of solid cattle slaughterhouse waste, manure, various crops, and municipal solid wastes are batch-digested in thermophilic process, a methane yield of 655 mL g -1 VS was obtained [64]. The approximate biogas yield estimated in Denmark by co-digestion for harvest residues including straw, stems, sugar beet toppings, and fibrous mater is 375 m 3 ton -1 , and animal manure (dough) was 200-500 m 3 ton -1 ; food industry waste, confectionary waste, and whey was 400-600 m 3 ton -1 ; slaughterhouse waste flotation sludge, animal fat, stomach and gut contents and blood was 550-1,000 m 3 ton -1 ; waste from paper industry was 400-800; sludge from gelatin and starch production was 700-900 m 3 ton -1 ; source-separated bio-wastes were 400-500 m 3 ton -1 ; and market waste was 500-600 m 3 ton -1 [65].…”
Section: Second Scenariomentioning
confidence: 92%
“…Furthermore, all of the co-digestion experiments clearly demonstrated a synergistic effect and strengthened the process stability of AD. Pagés-Díaz et al (2014) also pointed out that a mixture of different substrates with various characteristics could provide balanced nutrients and trace elements for anaerobic bacteria, and the diversity in the substrate composition would in turn promote more microorganism growth and accelerate the degradation of organic matter. Based on the above-mentioned analysis and discussion, it can be concluded that co-digestion is an excellent way to treat biomass wastes.…”
Section: The Methane Content and Specific Methane Yieldmentioning
confidence: 97%